CB2 receptors in neurons of the central nervous system - Avalos Fuentes, Jose Arturo (2019)
The endocannabinoid system is formed by endogenous ligands, biosynthetic enzymes and two classical receptors: CB1 and CB2. From a classical point of view, CB1 receptors are the “central cannabinoid receptors” expressed in neurons, whose function is the regulation of neurotransmitter release. On the other hand, CB2 receptors are considered the “peripheral cannabinoid receptors”, expressed in peripheral tissues. However, this classical view has changed over the years; new endogenous ligands, receptors isoform variants, new cellular locations such as mitochondria and new putative receptors GPR119 and GPR55 have been described. Thus, evidence indicates that the endocannabinoid system is more complex than once thought. In this regard, over the years, CB2R were found in glial cells where they modulate immune response; moreover, with the development of more selective ligands, antibodies and the characterization of their genes, the expression of CB2R in central neurons became evident. Thus, several questions arise concerning these findings. What is the function of these receptors in neurons? Do they also control the release of neurotransmitters and others? Here we review the state of the art for these findings and the possible future direction of this new line of research that contributes to understanding the complexity of the endocannabinoid system.